Audibility and Spectral-Ripple Discrimination Thresholds as Predictors of Word Recognition with Nonlinear Frequency Compression - Brennan, Marc A.; McCreery, Ryan W. (Journal of the American Academy of Audiology, 2021)
Background Nonlinear frequency compression (NFC) lowers high-frequency sounds to a lower frequency and is used to improve high-frequency audibility. However, the efficacy of NFC varies widely—while some individuals benefit from NFC, many do not. Spectral resolution is one factor that might explain individual benefit from NFC. Because individuals with better spectral resolution understand more speech than those with poorer spectral resolution, it was hypothesized that individual benefit from NFC could be predicted from the change in spectral resolution measured with NFC relative to a condition without NFC.Purpose This study aimed to determine the impact of NFC on access to spectral information and whether these changes predict individual benefit from NFC for adults with sensorineural hearing loss (SNHL).Research Design Present study is a quasi-experimental cohort study. Participants used a pair of hearing aids set to the Desired Sensation Level algorithm (DSL m[i/o]).Study Sample Participants were 19 adults with SNHL, recruited from the Boys Town National Research Hospital Participant Registry.Data Collection and Analysis Participants were seated in a sound-attenuating booth and then percent-correct recognition of words, and spectral-ripple discrimination thresholds were measured for two different conditions, with and without NFC. Because audibility is known to influence spectral-ripple thresholds and benefit from NFC, audibility was quantified using the aided speech intelligibility index (SII). Linear mixed models were generated to predict word recognition using the aided SII and spectral-ripple discrimination thresholds.Results While NFC did not influence percent-correct word recognition, participants with higher (better) aided SII and spectral-ripple discrimination thresholds understood more words than those with either a lower aided SII or spectral-ripple discrimination threshold. Benefit from NFC was not predictable from a participant's aided SII or spectral-ripple discrimination threshold.Conclusion We have extended previous work on the effect of audibility on benefit from NFC to include a measure of spectral resolution, the spectral-ripple discrimination threshold. Clinically, these results suggest that patients with better audibility and spectral resolution will understand speech better than those with poorer audibility or spectral resolution; however, these results are inconsistent with the notion that individual benefit from NFC is predictable from aided audibility or spectral resolution.
Keywords: hearing aids and assistive devices; speech perception; hearing science; frequency lowering; spectral resolution